Committees : how they work and how to work them - Anstey, Edgar (London, 1962)
Edgar Anstey's work gives a detailed account on the inner workings of the committee. Within a committee, different interests nearly always need to be represented when a decision must be taken, and contributions are required from people of different outlook or expert knowledge. A committee is often the only means of achieving a workable solution to a problem. This book attempts to analyse the functioning of different kinds of committee groups and to bring out the factors which make for efficiency and inefficiency. Types of committee and their purpose are discussed, as well as how to lead a discussion to bring out a genuine group view, the roles of chairman and secretary, how individuals influence committee decisions, good and bad tactics, and how to deal with difficult members.
Keywords: Legislation